World Economic Outlook : Interim Assessment, December 1997. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1998)
The economic and financial crisis that erupted in southeast Asia in July 1997 had continued to deepen and broaden as of December, and spillover effects from investor deteriorating confidence in emerging market economies were being felt throughout the global financial system. This special Interim Assessment of the World Economic Outlook revises regional and global economic projections made by the IMF staff, as published in the October 1997 issue, in light of the crisis; charts the buildup to the crisis and its onset and evolution; assesses effects on the advanced economies and on private financing for developing countries; and raises policy issues that the crisis has posed.